Välfärdsstat och ideologi: Den välfärdsideologiska förändringen inom fyra finländska partier under 1990-talet (Sociologisk Forskning, 2004)
The article investigates the changing welfare attitudes among Finnish parties during the 90s. During this particular period, the objective of maintaining full employment was abandoned and essential cutbacks in the Finnish welfare system were made. The main question in this article is whether these policies were made possible by changing conceptions of the idea of the welfare state among the political elites. The results show that parties in general adopted a more critical view of welfare spending, and a more positive attitude towards welfare pluralism and activation policies during the 90s, indicating a higher degree of convergence between parties. Rhetorically, these changes were mainly legitimized by arguments of economic necessities and international competitiveness.
Keywords: welfare state; welfare politics; welfare ideology; rhetoric; discourse